JENIS KELAMIN DAN ADAPTABILITAS KARIER: BUKTI EMPIRIS PADA MAHASISWA JABODETABEK DI ERA DINAMIKA DUNIA KERJA - Yohana Sri Rahayu; William Gunawan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Career adaptability refers to an individual's capacity to proactively cope with and adjust to challenges in career development. This study aims to examine gender differences in career adaptability among undergraduate students in the Greater Jakarta area (Jabodetabek). Despite the region's high labor market dynamics, research on students' adaptive readiness remains limited. Moreover, the use of the Career Adapt-Abilities Scale–Short Form (CAAS-SF) within the Indonesian context is still rare, highlighting a methodological gap addressed in this study. A total of 507 undergraduate students from various public and private universities participated in this study, which is part of the